Checklist of gobies (Teleostei: Gobiidae) of the Mediterranean Sea and a key for species identification - Kovačić, Marcelo (Zootaxa, 2020)
A checklist of 73 gobiid species (Teleostei: Gobiidae) recorded to date from the Mediterranean Sea is established following the evidence approach for checklists. The Mediterranean gobiofauna currently has 62 known native species and 11 alien species. An identification key to gobiid species known from the area is provided. The principles of character selection for the key are discussed.